Sistem Kewarisan Adat Suku Serawai pada Perkawinan Sistem Madu Kulau Semendau Belapiak Emas Perspektif Keadilan Gender di Kecamatan Kota Manna Kabupaten Bengkulu Selatan - Mariati, Dina; Yusmita, Yusmita; Yarmunida, Miti (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2026)
Abstracts: The inheritance law for daughters in the "madu kulau semendau belapiak emas" marriage system in Kota Manna District, South Bengkulu Regency, as viewed from the perspective of Islamic inheritance compared to Islamic law. It eliminates the position of daughters as heirs by lineage, whereas Surah An-Nisa verse 7 clarifies that men and women have equal rights to inherit property from parents and relatives. This study is a field research using a descriptive qualitative approach. The result of the study show that the Serawai tribal customary inheritance system in the "madu kulau semendau belapiak emas" marriage system, from a gender justice perspective in Kota Manna District, involves men marrying women by providing a dowry to the women's family, and after marriage, the wife is obliged to follow the husband. The inheritance distribution may occur while the testator is still alive, provided it is formally declared and witnessed by all heirs, who must reach a consensus through deliberation on the inheritance law to be applied. The wife's inheritance rights from her original family are lost, but she gains special inheritance rights from her husband, namely all control and management of the husband's wealth becomes the wife's right. The duties and rights of husband and wife in the "madu kulau semendau belapiak emas" marriage system are in accordance with the principles of gender justice from the perspective of inheritance law, which refers to the balance between rights and obligations in the family. Daughters are given the freedom to make decisions to choose "madu kulau" or not, with all its consequences, which represents gender justice and gender equality. The rights and responsibilities left by the husband to the family are continued by the wife. The wife controls the inheritance.Keywords: Indigenous Inheritance, Madu Kulau Semendau Belapiak Emas, Gender Justice. Abstrak:. Hukum waris anak perempuan pada perkawinan sistem madu kulau semendau belapiak emas di Kecamatan Kota Manna Kabupaten Bengkulu Selatan apabila dipandang dari sisi pewarisan Islam bertentangan dengan hukum Islam yaitu menghilangkan kedudukan anak perempuan sebagai ahli waris nasab sedangkan dalam surat An-Nisa ayat 7 menjelaskan bahwa laki-laki dan perempuan memiliki hak yang sama untuk mewarisi harta peninggalan dari orang tua maupun kerabat. Penelitian ini merupakan penelitian lapangan dengan menggunakan pendekatan kualitatif deskriptif. Hasil penelitian menunjukan bahwa sistem kewarisan adat suku Serawai pada perkawinan sistem  madu kulau semendau belapiak emas perspektif keadilan gender di Kecamatan Kota Manna bahwa laki-laki menikahi perempuan dengan memberikan uang antaran pada keluarga perempuan, yang telah disepakati melalui musyawarah keluarga dan setelah menikah istri wajib ikut suami. Bagian waris istri dari keluarga asal hilang tetapi mendapatkan hak waris istimewa dari suami  yakni semua penguasaan dan pengelolahan harta kekayaan suami menjadi hak istri. Kewajiban dan hak suami istri dari perkawinan sistem madu kulau semendau belapiak emas telah sesuai dengan prinsip keadilan gender dari sudut pandang hukum waris yang merujuk pada keseimbangan antara hak dan kewajiban dalam keluarga. Anak perempuan diberi kebebasan  dalam mengambil keputusan untuk memilih madu kulau atau tidak dengan segala konsekuensinya merupakan keadilan gender dan kesetaraan gender. Hak dan tanggung jawab yang ditinggalkan suami terhadap keluarga diteruskan oleh istri. Istri menguasai harta warisan.Kata kunci: Kewarisan Adat, Madu Kulau Semendau Belapiak Emas, Keadilan Gender.